Association between androgen receptor polymorphic CAG and GGC repeat lengths and cryptorchidism: A meta-analysis of case-control studies. Issue 5 (October 2018) - Wang, Y.; Wei, Y.; Tang, X.; Liu, B.; Shen, L.; Long, C.; Lin, T.; He, D.; Wu, S.; Wei, G.
Summary: Introduction: Previous studies have revealed the relationship between androgen receptor (AR) CAG and/or GGC polymorphisms and risk of cryptorchidism, yet the results have been elusive and controversial. Aim: To determine whether AR polymorphic CAG and/or GGC repeats are related to cryptorchidism. Study design: The relevant studies were obtained from PubMed, Embase, China National Knowledge Infrastructure, and Wanfang. The pooled odds ratios with 95% confidence intervals (CIs) were used to assess the strength of associations. Subgroup analyses were performed based on ethnicity and source of controls. Moreover, Begg's funnel plots and Egger's linear regression test were conducted to determine publication bias. Results: Eight case-control studies containing 321 patients and 784 normal controls were included. There was a significant association between longer CAG repeats and cryptorchidism risk (weighted mean difference (WMD) = 0.62; 95% CIs 0.06, 1.18; P = 0.031). Moreover, there was a significant association between the longer GGC repeats and cryptorchidism risk (WMD = 0.87; 95% CIs 0.04, 1.74; P = 0.040). There was significant association between the longer CAG repeats and bilateral cryptorchidism (WMD = 0.88; 95% CIs −0.18, 1.94; P = 0.011), while there was no significant association between the longer CAG repeats and unilateral cryptorchidism (WMD = −0.09; 95% CIs −0.50, 0.31; P = 0.554). There were significant associations between the longer GGC repeats and unilateral cryptorchidism (WMD = 0.88; 95% CIs −0.30, 2.05; P = 0.005) and bilateral cryptorchidism (WMD = 1.35; 95% CIs −0.52, 3.21; P = 0.000). Stratifying analysis revealed an association between longer CAG/GGC repeats and cryptorchidism in Caucasian populations from Europe (WMD = 0.73; 95% CIs 0.00, 1.46; P = 0.017), while there was no association with Asian populations. Discussion: This meta-analysis found that CAG/GGC repeats in the AR gene were longer in cryptorchidism patients compared to controls. Both the longer CAG repeats and GGC repeats in the AR gene were associated with cryptorchidism risk. The longer CAG repeats were associated with bilateral cryptorchidism, whereas the longer GGC repeats were associated with unilateral and bilateral cryptorchidism. Stratifying analysis revealed an association between longer CAG/GGC repeats and cryptorchidism in Caucasian populations from Europe, while there was no association between longer CAG/GGC repeats and cryptorchidism in Asian populations. Conclusion: The CAG/GGC repeats in the AR gene were longer in cryptorchidism than in controls. Longer CAG repeats may play a role in determining bilateral cryptorchidism, and longer GGC repeats may play a role in determining unilateral and bilateral cryptorchidism. These observations were more applicable to Caucasian populations. Table Androgen receptor CAG or GGC polymorphisms and risk of cryptorchidism. Weighted mean difference 95% confidence intervals P value CAG repeats vs cryptorchidism 0.62 (0.06, 1.18) 0.031 vs unilateral −0.09 (−0.50, 0.31) 0.554 vs bilateral 0.88 (−0.18, 1.94) 0.011 GGC repeats vs cryptorchidism 0.87 (0.04, 1.74) 0.040 vs unilateral 0.88 (−0.30, 2.05) 0.005 vs bilateral 1.35 (−0.52, 3.21) 0.000